We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
814
1
avatar+645 

 

Enter (A,B,C,D,E) in order below if A, B, C, D, and E are the coefficients of the partial fractions expansion of \(f(x) = 3\cdot\frac{x^4+x^3+x^2+1}{x^2+x-2} = Ax^2 + Bx + C + \frac{D}{x+2} + \frac{E}{x-1}.\)
 

 Mar 9, 2018
 #1
avatar+23041 
0

 Enter (A,B,C,D,E) in order below if A, B, C, D, and E are the coefficients of the partial fractions expansion of

\(\displaystyle f(x) = 3\cdot\frac{x^4+x^3+x^2+1}{x^2+x-2} = Ax^2 + Bx + C + \frac{D}{x+2} + \frac{E}{x-1}. \)

f(x) = 3\cdot\frac{x^4+x^3+x^2+1}{x^2+x-2} = Ax^2 + Bx + C + \frac{D}{x+2} + \frac{E}{x-1}.

 

\(\small{ \begin{array}{|rcll|} \hline 3\cdot\dfrac{x^4+x^3+x^2+1}{x^2+x-2} &=& 3\cdot\dfrac{x^4+x^3+x^2+1}{(x+2)(x-1)} \\ \\ \hline \\ 3\cdot\dfrac{x^4+x^3+x^2+1}{(x+2)(x-1)} &=& Ax^2 + Bx + C + \dfrac{D}{x+2} + \dfrac{E}{x-1} \qquad | \qquad \cdot (x+2)(x-1) \\ \hline \end{array} }\)

 

\(\begin{array}{|rcll|} \hline 3(x^4+x^3+x^2+1) &=& A\cdot x^2(x+2)(x-1) + B\cdot x(x+2)(x-1) \\ &+& C\cdot (x+2)(x-1) + D\cdot (x-1) + E\cdot(x+2) \\ \hline \end{array}\)

 

\(\small{ \begin{array}{lrcll} \hline \mathbf{x = 1:} & 3(1 +1+1+1) &=& A\cdot 0 + B\cdot 0 + C\cdot 0 + D\cdot 0 + E\cdot (1+2) \\ & 12 &=& 3E \\ & \mathbf{E} &\mathbf{=}& \mathbf{4} \\ \\ \hline \mathbf{x = -2:} & 3(16-8+4+1) &=& A\cdot 0 + B\cdot 0 + C\cdot 0 + D\cdot (-2-1) + E\cdot 0 \\ & 3\cdot 13 &=& -3D \\ & 13 &=& - D \\ & \mathbf{D} &\mathbf{=}& \mathbf{-13} \\ \\ \hline \mathbf{x = 0:} & 3(0+0+0+1) &=& A\cdot 0 + B\cdot 0 + C\cdot(0+2)(0-1) + D\cdot (0-1) + E\cdot (0+2) \\ & 3 &=& -2C-D+2E \\ & 3 &=& -2C-(-13)+2\cdot 4 \\ & 3 &=& -2C+13+8 \\ & 3 &=& -2C+ 21 \\ & 2C &=& 21 -3 \\ & 2C &=& 18 \\ & \mathbf{C} &\mathbf{=}& \mathbf{9} \\ \\ \hline \mathbf{x = -1:} & 3(1 -1+1+1) &=& A\cdot 1(-1+2)(-1-1) + B\cdot (-1)(-1+2)(-1-1) \\ & &+& C\cdot (-1+2)(-1-1) + D\cdot (-1-1) + E\cdot (-1+2) \\ & 6 &=& -2A+2B-2C-2D+E \\ & 6 &=& -2A+2B-2\cdot 9 +2\cdot 13+ 4 \qquad | \qquad : 2 \\ & 3 &=& -A+B-9 +13+ 2 \\ & 3 &=& -A+B+6 \\ & \mathbf{-A+B} &\mathbf{=}& \mathbf{-3} \qquad (1) \\ \\ \hline \mathbf{x = 2:} & 3(16+8+4+1) &=& A\cdot 4(2+2)(2-1) + B\cdot 2(2+2)(2-1) \\ & &+& C\cdot (2+2)(2-1) + D\cdot (2-1) + E\cdot (2+2) \\ & 87 &=& 16A+8B+4C+D+4E \\ & 87 &=& 16A+8B+4\cdot 9 -13+4\cdot 4 \\ & 87 &=& 16A+8B+36 -13+16 \\ & 87 &=& 16A+8B+39 \\ & 16A+8B&=& 87 - 39 \\ & 16A+8B&=& 48 \qquad | \qquad : 8 \\ & \mathbf{2A+B} &\mathbf{=}& \mathbf{6} \qquad (2) \\ \hline \end{array} }\)

 

\(\begin{array}{|lrclcrclr|} \hline (2) & 2A+B &=& 6 &\qquad & -A+B &=& -3 & (1) \\ & & & &\qquad & B &=& -3+A \\ & 2A-3+A &=& 6 \\ & 3A &=& 9 \\ & \mathbf{A } &\mathbf{=}&\mathbf{ 3} \\ & & & &\qquad & B &=& -3+3 \\ & & & &\qquad & \mathbf{B} &\mathbf{=}&\mathbf{ 0} \\ \hline \end{array} \)

 

\(\displaystyle f(x) = 3\cdot\frac{x^4+x^3+x^2+1}{x^2+x-2} = 3x^2 + 0\cdot x + 9 - \frac{13}{x+2} + \frac{4}{x-1}\)

 

\(\mathbf{(A,B,C,D,E) = (3,0,9,-13,4)}\)

 

laugh

 Mar 9, 2018

29 Online Users